Reading weakness in children, according to the perceptions of kindergarten teachers - عبد الله داود سعاد (Journal of College of Education, 2021)
Reading impairment is not an organic disease but rather a condition of neurological origin and is not caused by environmental, emotional or educational factors, and its concept coincides with the concept of learning difficulties, as the form of significant difficulties is manifested in discovering and using the skills of listening, speaking, reading, memory, or mathematical abilities. These disorders are characterized by being internal disturbances in the individual that are supposed to be due to a functional deficiency in the central nervous system, and they can occur throughout life. They can also be accompanied by problems in the behavior of self-regulation, social perception and social interaction without these matters in themselves constituting an educational difficulty, and to achieve Objective of the current research The researcher has adopted the Ramli (2019, Ramli) scale in the current research as it is consistent with the research sample The research consists of three areas, and for each field a number of paragraphs, in the field of knowledge of reading impairment it consists of (17) paragraphs. As for the field of diagnosing reading impairment, it consists of (10) paragraphs while the field of treatment is (9). It was presented to a group of experts specializing in the field of childhood and psychology, and the validity of the construction was verified through some of its indicators. The stability was also assessed by the Vakronbach method (0.89) and after verifying the psychometric properties of the scale as it was applied to a sample of (150) teachers who were selected. In a random way, and after verifying the data, it was subjected to statistical treatment using statistical methods (Pearson Correlation Coefficient, T- The following results were reached: Reading impairment is a familiar term, and teachers are aware of this disorder, and it is not difficult for a kindergarten teacher to pay attention to children with him. As for the recommendations, we call on the Ministry of Education to use reading impairment measures for Riyadh children in order to discover and treat impairment. She suggested conducting a comparative study. In the reading weakness of the children of Riyadh, between the villages and the city.